Co-regulation of senescence-associated genes by oncogenic homeobox proteins and polycomb repressive complexes - Martin, Nadine (Landes Bioscience, 2013)
Cellular senescence is a stable cell cycle arrest that can be induced by stresses such as telomere shortening, oncogene activation or DNA damage. Senescence is a potent anticancer barrier that needs to be circumvented during tumorigenesis. The cell cycle regulator p16(INK4a) is a key effector upregulated during senescence. Polycomb repressive complexes (PRCs) play a crucial role in silencing the INK4/ARF locus, which encodes for p16(INK4a), but the mechanisms by which PRCs are recruited to this locus as well as to other targets remain poorly understood. Recently we discovered the ability of the homeobox proteins HLX1 (H2.0-like homeobox 1) and HOXA9 (Homeobox A9) to bypass senescence. We showed that HLX1 and HOXA9 recruit PRCs to repress INK4a, which constitutes a key mechanism explaining their effects on senescence. Here we provide evidence for the regulation of additional senescence-associated PRC target genes by HLX1 and HOXA9. As both HLX1 and HOXA9 are oncogenes implicated in leukemogenesis, we discuss the implications that the collaboration between Homeobox proteins and PRCs has for senescence and cancer.